ISO 9126 Quality Model for Evaluating of Student Portal: Al-Madinah International University (Case study) - Al Moaiad, Yazeed; Abu Bakar, Zainab; Zamin, Norshuhani; Yahya, Yazrina (2023)
E-learning is a teaching system that involves electronic resources such as computers and the Internet, and the student portal is an essential tool that supports learning in universities. However, there is a limited evaluation model for educational websites. Therefore, a framework is required to guide the creation of such a model. The study conducted evaluates the quality of the student portal at Al-Madinah International University based on ISO 9126 quality model from the student's perspective, and the results show a good quality portal. Nonetheless, students suggest improvements to enhance its effectiveness, ease of use, and learning process.